Establishing RDCS in CO MESA: Egyptian exporters' perspectives - El-Nakib, Islam; Roberts, Charles (Promet - Traffic&Transportation, 2008)
The role of supply chains has been significant in strengtheningthe competitiveness of interna tiona[ trade among countries.Regional Distribution Centres (RDCs) are among the remarkabledrivers of any international trade supply chains. The Egyptianexports face severe competition in the international marketwhich has led the Egyptian government to join regional tradeblocks such as the Common Market for Eastern and SouthernAfrica (COMESA) for the aim of establishing export channelsto new markets. Therefore, applying the concept of RDCs wasexamined to enhance the performance of Egyptian exportswhich are facing high competition in the EU, US, and Asianmarkets. Thus, the purpose of this research is to study the associatedaspects to this area of interest based on a survey whichhas targeted the Egyptian exporters who are directly dealingwith the CO MESA to cover several issues regarding the tradebetween Egypt and CO MESA. Moreover, this survey has alsoincluded the analysis of the reasons that make the CO MESAprefer other international products rather than the Egyptianproducts, and the attitudes towards the proposed selection ofEgypt's RDCs in COMESA. In addition, this survey is alsoidentifying the main features of the Egyptian exports comparedwith the foreign exports in COMESA and the recommendedaction to be taken towards the establishment of the EgyptianRDCs in CO MESA.